2011
DOI: 10.1016/j.appet.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Training inhibitory control. A recipe for resisting sweet temptations

Abstract: When inhibitory control is lacking, people are more prone to indulge in high calorie food. This research examined whether training to inhibit food-related responses renders one less susceptible to temptations of high calorie food. Trait chocolate lovers were divided into three conditions: participants either consistently inhibited responding to chocolate stimuli (chocolate/no-go condition), consistently responded to chocolate stimuli (chocolate/go condition), or responded to chocolate stimuli only during half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
290
5
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(320 citation statements)
references
References 27 publications
20
290
5
5
Order By: Relevance
“…short term outcome). This finding is not in line with Houben and Jansen (2011) who did find an effect of the training looking at food intake, where food intake was lower in the intervention group. This discrepancy could be due to the food types used as the nogo cues.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…short term outcome). This finding is not in line with Houben and Jansen (2011) who did find an effect of the training looking at food intake, where food intake was lower in the intervention group. This discrepancy could be due to the food types used as the nogo cues.…”
contrasting
confidence: 54%
“…Earlier studies either focused on the short term outcomes after one go/no-go training (Houben & Jansen, 2011) or the long term results after multiple trainings (Veling et al, 2014). In contrast to Houben and Jansen (2011), the present study went beyond one no-go food type, and extended it with three unhealthy food types trained for inhibition.…”
mentioning
confidence: 88%
“…For example, consistent pairing of food-related pictures to stopping in a go/no-go or stop-signal paradigm reduces subsequent food consumption (e.g., Houben & Jansen, 2011;Lawrence, Verbruggen, Morrison, Adams, & Chambers, 2015), and may even lead to weight loss Veling, van Koningsbruggen, Aarts, & Stroebe, 2014). Recent meta-analyses indicate that no-go/stop training has small but robust effects on food and alcohol consumption (Allom, Mullan, & Hagger, 2015;Jones et al, 2016).…”
Section: Applications Of Automatic Inhibitionmentioning
confidence: 99%
“…Several studies have found that consistent pairing of food-related pictures to stopping in a go/no-go or stop-signal-paradigm reduced subsequent food consumption (e.g. Houben, 2011;Houben & Jansen, 2011;Lawrence, Verbruggen, Adams, & Chambers, 2013;Veling, Aarts, & Papies, 2011;Veling, Aarts, & Stroebe, 2012). Furthermore, a similar procedure with alcohol-related stimuli reduced alcoholintake in the laboratory (Jones & Field, 2013) and even self-reported weekly alcohol intake of heavy drinking students (Houben, Havermans, Nederkoorn, & Jansen, 2012; but see Jones & Field, 2013).…”
Section: What Is Learned During Conditioning Of Inhibitory Control?mentioning
confidence: 99%